(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of this research is to verify the reliability of the instrument used to collect the information, applying Cronbach’s Alpha, and the validation of the hypothesis through an Analysis of Variance (ANOVA). Cronbach’s Alpha is obtained in Excel. The survey is used with the questions shown in the Check List, applied in a vehicle assembly plant. The instrument used and the validation of the hypothesis are subjects of a research work, referring to the production planning in the vehicle assembler Ciauto Cia. Ltda. specifically for the HAVAL M4 AC 1.5 TM 5P 4X2 Model, where for the verification of the reliability of the instrument used a Cronbach’s Alpha of 0.57 was obtained, which indicates that the instrument used has a poor reliability according to the scale in the Cronbach’s Reliability table. As for the validation of the hypothesis by applying an ANOVA, a calculated F - Fisher of 28.25 was obtained, compared to a tabulated F - Fisher of 2.996, so the null hypothesis (H0) should be rejected in favor of the alternative hypothesis (Ha).